Systematic serialisation of array-based architectures - Luk,WWC (Integration the VLSI Journal, 1993)
This paper describes the use of Ruby, a language of functions and relations, to develop serialised implementations of array-based architectures. Our Ruby expressions contain parameters which can be varied to produce a wide range of designs with different space-time trade-offs. Such expressions can be obtained by applying correctness-preserving transformations to an initial simple description. This approach provides a unified treatment of serialisation schemes similar to LPGS (Locally Parallel Globally Sequential) and LSGP (Locally Sequential Globally Parallel) partitioning methods, and will be illustrated by the development of a variety of circuits for convolution. © 1993.